(NfIZIKO(B-(NHIMI^ESKIE MODELI NOWEJ[IH PROCESSOW WYWETRIWANIQ (B/s - (NkA[IK(B, (NsERGEJ aLEKSEEWI^s; (NmAZILOW(B, (NwLADIMIR nIKOLAEWI^s; (NpAWLOW(B, (Ns(B.(Nf(B.s; (NiNSTITUT ZEMNOJ KORY so an sssrs ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 87-92s
Keywords: (NwYWETRIWANIEs; (NgORNYE PORODYs; (NiMITACIONNOE MODELIROWANIEs; (NmINERALOOBRAZOWANIEs